The Discourse of Sheikh Amran Waly Al Khalidi on Sufistic Epistemology and Qur'anic Interpretation - Ramli, Ramli; Handoyo, Budi; Efendi, Sumardi; Fajeri, Fajeri; Ferdikaandin, Dede (JURNAL AT-TURAS, 2025)
Sheikh Amran Waly is a prominent scholar in Aceh with a congregation spread across Southeast Asia, yet his teachings are often rejected by Acehnese scholars. One of the most controversial ideas is his interpretation of Dhamir Huwa in Surah Al-Ikhlas, which he associates with Muhammad as Insan Kamil. This study aims to conduct an epistemological and interpretative analysis of this understanding using a qualitative-descriptive approach. Data were collected through interviews, observations and documentation. The findings reveal that Sheikh Amran Waly's interpretation of Dhamir Huwa is derived from the teachings of Sheikh Abdul Karim Al-Jili and Ibn Arabi. This study also concludes that Sheikh Amran Waly's understanding of Dhamir Huwa is built on a valid epistemological and interpretative framework rooted in the thoughts of previous scholars. The contribution of this research lies in elucidating the continuity and adaptation of Wujudiyah thought in Aceh, particularly through Sheikh Amran Waly's synthesis of ishari and ibari dimensions, thereby providing a nuanced perspective on contemporary Wujudiyah discourse.